Peningkatan Kemampuan Berfikir Kritis dan Pemecahan Masalah Matematis Siswa antara Siswa yang Diberi Pelajaran Kooperatif Tipe TPS Square dan TPS Share - Juliandri Yani; Israq Maharani; Nabila Faiza Dalimunthe; Fitry Khairany Pulungan; Nurhabibi Fakhri (Program Studi Pendidikan Matematika FKIP UNIVA Medan, 2024)
This study aimed to assess the difference in improving critical thinking and mathematical problem-solving abilities among students receiving cooperative learning with the TPS Square and TPS Share methods. The experimental method utilized a pretest-posttest control group design involving two groups of students from a secondary school. One group received instruction using the TPS Square method, while the other group utilized the TPS Share method. Research instruments comprised tests on critical thinking and mathematical problem-solving abilities. Data collected were analyzed using non-parametric statistical techniques. The results of the analysis revealed a significant improvement from the pretest to the posttest, as reflected in higher test scores in the final stage. Based on the t-test calculations, the critical value (t-table) at a significance level of 5% (α = 0.05) was found to be 2.514. With the computed t-value exceeding the critical value (2.157 > 2.514), it can be concluded that there is a significant difference in the average critical thinking and mathematical problem-solving abilities before and after instruction using the cooperative learning models TPS and TPSq among the students of grade XII at SMA Al Washliyah 1 Medan during the academic year 2022-2023.